2010
DOI: 10.1007/s11738-010-0618-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoranthene-induced production of ethylene and formation of lysigenous intercellular spaces in pea plants cultivated in vitro

Abstract: The effect of increasing concentration of polycyclic aromatic hydrocarbon (PAH) fluoranthene (FLT; 0.1, 1 and 5 mg l -1 ) on the growth, ethylene production and anatomy of stems of 21-day-old pea plants cultivated in vitro in MS medium, with or without FLT, enriched with 0.1 mg l -1 indole-3-acetic acid (IAA) or with combination of 0.1 mg l -1 IAA ? 0.1 mg l -1 N 6 -benzyladenine (BA) were investigated. The low concentration of 0.1 mg l -1 FLT, in both IAA-and IAA ? BA-treated plants, significantly stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is known that FLC and PAHs cause in plants the oxidative stress accompanied by the increased production of ROS [Liu et al 2018b;Shen et al 2019a]. ROS production in roots can alter the root anatomy and can cause the formation of the intercellular spaces via the programmed cell death [Svobodníková et al 2020], which could be also initiated with the increased level of ethylene [Kummerová et al 2010;Váňová et al 2011]. In our study we did not observe the formation of lysigenous intercellular spaces in the roots (or stems) of experimental plants, as well as no significantly higher levels of ethylene in roots (data not presented) but about the oxidative stress could report the higher levels of malondialdehyde analysed in leaves and presented in previous study by Lónová et al [2023].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that FLC and PAHs cause in plants the oxidative stress accompanied by the increased production of ROS [Liu et al 2018b;Shen et al 2019a]. ROS production in roots can alter the root anatomy and can cause the formation of the intercellular spaces via the programmed cell death [Svobodníková et al 2020], which could be also initiated with the increased level of ethylene [Kummerová et al 2010;Váňová et al 2011]. In our study we did not observe the formation of lysigenous intercellular spaces in the roots (or stems) of experimental plants, as well as no significantly higher levels of ethylene in roots (data not presented) but about the oxidative stress could report the higher levels of malondialdehyde analysed in leaves and presented in previous study by Lónová et al [2023].…”
Section: Discussionmentioning
confidence: 99%
“… 159 The mechanisms of the action of bacterial phytohormones in plant growth regulation and their development have been reviewed by Kudoyarova et al 160 Some studies have indicated that the application of biochar partly boosts plant growth and development by activating the gibberellin pathway 161 and enhancing the transcription of auxin- and brassinosteroid-related genes, which play a key role in inducing systemic stress tolerance in plants. 162 …”
Section: Biochar-based Pgpb: Key Considerations For Phytoremediationmentioning
confidence: 99%